Nautical Eco-Lexicon of Lamaholot Language of Bahinga Village - Fransiska Jone Mare (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
This study examines the treasury of eco-lexicon in order to reveal the level of society's knowledge on the diversity of lexicon, the metaphorical expressions and the mythology of the nautical matter of the language. To achieve these objectives, I made use of quantitative-qualitative research method. I collected the data by using observation, interview and questionnaire methods. The results of the study show there are 87 nautical nominal laxicons in the form of base, 24 lexicons in the form of phrase, and 16 lexicons in the form of verb